Dimensions for revitalizing happiness in the classroom: innovative spaces in higher education - Cerdá Suárez, Luis Manuel (My University, 2020)
As a result of the increasing importance of the discipline of Positive Psychology in several academic areas, positive evaluations of life satisfaction are linked to happiness and numerous studies have addressed overall satisfaction with life in certain domains, including learning and teaching. In this sense, happiness and well-being in the classroom become compulsory in Higher Education. In usual educational practice, there are many theoretical and empirical studies focused on analyzing whether the website usability in learning or rather the personal characteristics of the students, are the most influential factors in their satisfaction. The objective of this work is to evaluate the impact of those factors in order to improve the happiness in the classroom in Higher Education, based on the existing pedagogical and business literature. In this paper, a wide spatial representation of cross-sectional nature has been conducted at universities in Spain, Portugal, Mexico and Chile. Within the framework of an international research of teaching innovation supported by the Pontificia Universidad Catolica de Valparaiso (PUCV, Chile), a questionnaire was carried out to collect data and a factorial design for evaluating the impact of different combinations of website usability on happiness in the classroom, considering some personal characteristics of the students. The total number of students in this research was 203 and the main results of this study allow to characterize those factors and quantify its relevance to different levels of performance in the classroom.
Keywords: dimensions; teaching; happiness; classroom; higher education; WOS(2)